Islamic Education Curriculum Management in the Digital Era: A Qualitative Study on Learning Technology Integration - Rindi Septi Ani; Iis Arifudin; Ria Yulia Gloria; Djohan Rochanda Wiradinata (Journal of Mathematics Instruction, Social Research and Opinion, 2025)
This research aims to analyse and describe the management of the Islamic Education curriculum at Al-Multazam 2 Integrated Islamic Junior High School Kuningan, particularly concerning the integration of learning technology in the digital era. The study employs a descriptive qualitative approach, focusing on the processes of planning, organising, implementing (or actuating), and supervising (or controlling) the digital-based curriculum. Data were collected through interviews with teachers, the vice principal for curriculum, the vice principal for student affairs, and grade 7 students, with a sample of four classes observed. Furthermore, the researcher also conducted in-depth observation and documentation studies. Data analysis was conducted in four stages, as outlined by Miles and Huberman. The results indicate that the curriculum management at Al-Multazam 2 Integrated Islamic Junior High School has systematically implemented the POAC (Planning, Organising, Actuating, Controlling) framework to balance the demands of digitalisation and the strengthening of Islamic values. Planning is carried out collaboratively to design digital lesson plans (RPP) and integrate Islamic values into the content. Implementation is conducted through a blended learning model using platforms such as Google Classroom, as well as interactive media (Canva, Quizizz). The School IT Team and the Teacher Professional Development Committee support the organisation. Meanwhile, Controlling (Supervision) is carried out through academic supervision and comprehensive evaluation (cognitive, affective, and spiritual/Tahfizh). Despite facing challenges in teacher competency and digital ethics risks among students, the school successfully implemented strategies for continuous human resource strengthening and content monitoring. The application of this POAC management strategy has a positive impact on improving learning quality, accessibility, and the development of students' digital literacy. This proves that Islamic educational institutions can adapt to global changes while maintaining and strengthening their Islamic value identity.